Prognostic Value of Myogenic Differentiation in Dedifferentiated Liposarcoma. (June 2020) - Kurzawa, Pawel; Mullen, John T.; Chen, Yen-Lin; Johnstone, Sarah E.; Deshpande, Vikram; Chebib, Ivan; Nielsen, G.P.
Abstract : Myogenic differentiation (MD) has been claimed to be a poor prognostic factor in dedifferentiated liposarcoma (DDLPS). To validate this, the prognostic significance of MD in a uniformly treated cohort of DDLPS was assessed. A cohort of patients that have been uniformly treated at one institution for DDLPS of the retroperitoneum and pelvis were stained with smooth muscle actin (SMA) and desmin and semiquantitatively scored for staining focality and strength. Clinical and survival data was collected, and the prognostic significance of MD was evaluated. A total of 50 patients with uniformly treated DDLPS were evaluated. SMA ( P =0.052) and a combined score of MD (SMA+desmin) showed a statistically significant decrease in 5-year disease-free survival ( P =0.002) in univariate analysis and in multivariate testing combined MD trended toward significance ( P =0.052). Combined MD was associated with a decreased OS in multivariate analysis ( P =0.004). In a uniformly treated cohort of DDLPS stained for myogenic markers, a combined myogenic score was associated with poor overall survival in multivariate analysis. However, the difference in groups was slight and the clinical application is limited.